Kaji performa mesin refrigerasi siklus kompresi uap dengan refrigeran R134a dan refrigeran hidrokarbon sebagai drop-in substitute pada dengan alat ekspansi berbeda - Azridjal Aziz; Iqbal Parija; Rahmat Iman Mainil (BKS-TM Indonesia, 2025)
Refrigerant is an essential working fluid in refrigeration system. However, the use of synthetic refrigerant such as R-134a is now restricted due to its high Global Warming Potential (GWP) value. As an alternative, MC-134 as hydrocarbon refrigerant offers more environmentally friendly solution. This research aims to compare the performance of R-134a and MC-134 in a vapor compression refrigeration cycle system, as well as analyze the influence of expansion devices, namely capillary pipes and Thermostatic Expansion Valves (TEV). The test results show that for R-134a, increasing the length of the capillary pipe, increases the Coefficient of Performance (COP) by 20.83% due to decrease in compression work. In contrast, for MC-134, there is decrease in COP by 3.35%. TEV provides the best performance with an increase in refrigeration effect of 6.05% and COP of 25.07%. However, TEV is not suitable for MC-134 because the low condensing pressure inhibits the phase change to liquid. In the use of 1.25 m and 1.5 m capillary pipes, MC-134 even has a higher COP of up to 16.65% compared to R-134a. Despite this, MC-134 still shows potential as a replacement for R-134a, with 30% of the mass capable of producing twice the refrigeration effect and 7.52% lower electric current consumption.